2023
DOI: 10.1002/cmdc.202300397
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in Mitochondria‐Localized Luminescent Ruthenium(II) Metallodrugs as Anticancer Agents

Sushree Aradhana Patra,
Gurunath Sahu,
Sanchita Das
et al.

Abstract: Presently, the most effective way to transport drugs specifically to mitochondria inside the cells is of pharmacophoric interest as mitochondria are recognized as one of the most important targets for new drug design in cancer diagnosis. To date, there are many reviews covering the photophysical, photochemical, and anticancer properties of ruthenium(II) based metallodrugs owing to their high interest in biological applications. There are, however, no reviews specifically covering the mitochondria‐localized lum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 125 publications
(130 reference statements)
0
2
0
Order By: Relevance
“…This result suggested that there is slow partial substitution of the negatively charged thiolato ligand in 1a with an uncharged ligand or ligands to produce positively charged complexes, since lipophilic positively charged drugs are known to target the mitochondria. 62,63 Unlike for cytotoxic Re( i ) isonitrile complexes, 28,29 prolonged treatment with 1a did not affect the mitochondrial morphology (middle row in Fig. 12b).…”
Section: Resultsmentioning
confidence: 89%
“…This result suggested that there is slow partial substitution of the negatively charged thiolato ligand in 1a with an uncharged ligand or ligands to produce positively charged complexes, since lipophilic positively charged drugs are known to target the mitochondria. 62,63 Unlike for cytotoxic Re( i ) isonitrile complexes, 28,29 prolonged treatment with 1a did not affect the mitochondrial morphology (middle row in Fig. 12b).…”
Section: Resultsmentioning
confidence: 89%
“…The previously studied silver complexes with 1,2,4-triazole derivatives exhibit luminescent properties [ 52 , 53 , 54 ], which are very important in the design of promising metal-containing drugs [ 55 , 56 , 57 , 58 ]. It was also previously shown that silver has a high affinity for the sulfur atom, forming strong linear compounds or layers [ 59 , 60 , 61 ].…”
Section: Introductionmentioning
confidence: 99%